2004
DOI: 10.1111/j.1467-8624.2004.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and Mothers at Play With Their 2‐ and 3‐Year‐Olds: Contributions to Language and Cognitive Development

Abstract: Father-child and mother-child engagements were examined longitudinally in relation to children's language and cognitive development at 24 and 36 months. The study involved a racially/ethnically diverse sample of low-income, resident fathers (and their partners) from the National Early Head Start evaluation study (n=290). Father-child and mother-child engagements were videotaped for 10 min at home during semistructured free play, and children's language and cognitive status were assessed at both ages. Fathers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
539
6
30

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(632 citation statements)
references
References 62 publications
42
539
6
30
Order By: Relevance
“…In line with previous studies (e.g. Linver et al, 2002;Tamis-LeMonda et al, 2004), responsiveness (PPVT: z = 3.9, p<0.001; VCR: z = 2.4, p = 0.016), involvement (PPVT: z = 3.4, p<0.001), and family dysfunction (PPVT: z = 2.9, p = 0.004; VCR: z = 2.0, p = 0.048) were all significant mediators of maternal education. Responsiveness (PPVT: z = 3.9, p<0.001; VCR: z = 2.5, p = 0.012), involvement (PPVT: z = 3.3, p<0.001; VCR: z = 2.3, p = 0.023) and family dysfunction (PPVT: z = 2.9, p = 0.004; VCR: z = 2.0, p = 0.042) were also significant mediators of family income.…”
Section: Mediation Under Different Prenatal Smoking and Birth Weight supporting
confidence: 93%
“…In line with previous studies (e.g. Linver et al, 2002;Tamis-LeMonda et al, 2004), responsiveness (PPVT: z = 3.9, p<0.001; VCR: z = 2.4, p = 0.016), involvement (PPVT: z = 3.4, p<0.001), and family dysfunction (PPVT: z = 2.9, p = 0.004; VCR: z = 2.0, p = 0.048) were all significant mediators of maternal education. Responsiveness (PPVT: z = 3.9, p<0.001; VCR: z = 2.5, p = 0.012), involvement (PPVT: z = 3.3, p<0.001; VCR: z = 2.3, p = 0.023) and family dysfunction (PPVT: z = 2.9, p = 0.004; VCR: z = 2.0, p = 0.042) were also significant mediators of family income.…”
Section: Mediation Under Different Prenatal Smoking and Birth Weight supporting
confidence: 93%
“…Play is important to healthy brain development. [4][5][6] It is through play that children at a very early age engage and interact in the world around them. Play allows children to create and explore a world they can master, conquering their fears while practicing adult roles, sometimes in conjunction with other children or adult caregivers.…”
Section: The Benefits Of Playmentioning
confidence: 99%
“…Parental sensitivity can be understood as an awareness of the child's verbal and nonverbal cues (Wallace, Roberts, & Ladder, 1998). Research has consistently indicated that maternal and paternal sensitivity is positively linked to young children's language development during the infant and toddler years (Baumwell, Tamis-LeMonda, & Bornstein, 1997;Fish & Pinkerman, 2003;Tamis-LeMonda et al, 2004).…”
Section: Parent-child Interactionsmentioning
confidence: 99%
“…The family environment of the home, as measured by the quality of parent/child interactions, parental language, and the provision of stimulating/sensitive caregiving, has been found to be an important proximal predictor of children's development (Bradley, Corwyn, Burchinal, Pipes-McAdoo, & Garcia Coll, 2001;Hoff-Ginsberg, 1991;Pan, Rowe, Singer, & Snow, 2005;Pancsofar & Vernon-Feagans, 2006; Tamis-Lemonda, Shannon, Cabrera, & Lamb, 2004). These studies have generally shown, through observation and questionnaires, that mothers who are more sensitive and engaging to their children during interactions and provide a more stimulating home environment, have children who are more skilled cognitively, linguistically, and socially.…”
Section: Introductionmentioning
confidence: 99%